1999
DOI: 10.1128/mcb.19.3.1864
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase Activity Is Sufficient To Allow Transformed Cells To Escape from Crisis

Abstract: The introduction of simian virus 40 large T antigen (SVLT) into human primary cells enables them to proliferate beyond their normal replicative life span. In most cases, this temporary escape from senescence eventually ends in a second proliferative block known as "crisis," during which the cells cease growing or die. Rare immortalization events in which cells escape crisis are frequently correlated with the presence of telomerase activity. We tested the hypothesis that telomerase activation is the critical st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
0
5

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(100 citation statements)
references
References 61 publications
2
93
0
5
Order By: Relevance
“…Only a small fraction of these cells survive a subsequent crisis and proliferate indefinitely. Furthermore, the introduction of telomerase into cells expressing SV40 large T antigen enabled human fibroblasts and embryonic kidney and pancreatic cells to escape from crisis (Counter et al, 1998;Halvorsen et al, 1999;Zhu et al, 1999).…”
Section: Human Pulmonary Microvascular Endothelial Cell Linementioning
confidence: 99%
“…Only a small fraction of these cells survive a subsequent crisis and proliferate indefinitely. Furthermore, the introduction of telomerase into cells expressing SV40 large T antigen enabled human fibroblasts and embryonic kidney and pancreatic cells to escape from crisis (Counter et al, 1998;Halvorsen et al, 1999;Zhu et al, 1999).…”
Section: Human Pulmonary Microvascular Endothelial Cell Linementioning
confidence: 99%
“…The normal human primary ®broblasts (HFF) used in these studies were Basinger cells (Halvorsen et al, 1999). Cells were cultured according to the procedure described recently (Smilenov et al, 1999).…”
Section: Cell Culture and Retroviral Infectionmentioning
confidence: 99%
“…We determined the e ects of ectopic expression of hTERT in two primary A-T ®broblast cell strains GM02052 and GM05823. Stable GM02052 and GM05823 cell populations (hTERT+) were generated by infection of GM02052 cells at 36 PD and GM05823 at 40 PD with hTERT-expressing retrovirus as previously described (Halvorsen et al, 1999;Ouellette et al, 1999). GM02052 and GM05823 cells were also infected with control empty retroviral construct.…”
Section: Expression Of Htert In Human Ataxia Telangiectasia Fibroblasmentioning
confidence: 99%
“…Indeed, it has been recently shown that overexpression of the human telomerase reverse transcriptase (h-TERT) allows SV40 T-Ag-transformed cells, derived from different tissues, to bypass the crisis step and to promote indefinite life span. 4,5 Nevertheless, the differentiation process of certain cell types, such as preadipocytes, is clearly blocked by SV40 T-Ag expression. 6 Differentiation of preadipocytes into adipocytes (i.e.…”
Section: Introductionmentioning
confidence: 99%